First Report of Adult Aedes aegypti (Diptera: Culicidae) Resistance to Pyrethroids in Argentina - Harburguer, Laura Vanesa (2022)
Severe human arboviral diseases can be transmitted by the mosquito Aedes aegypti (Linnaeus), including dengue, chikungunya, Zika, and yellow fever. Adult control using spatial sprays with adulticides is recommended only when dengue outbreaks occur. In Argentina, mainly pyrethroids, like cis-permethrin, have been used as an adulticide, especially since 2008. The evolution and spread of resistance to insecticides is a major concern for vector control. This study reports for the first time pyrethroid resistance in Ae. aegypti adults from Argentina, in the city of Salvador Mazza (Salta). WHO discriminating doses of 0.75% were used for permethrin, 0.05% for deltamethrin, and 5% for malathion. Also the discriminating dose for cis-permethrin (0.6%) was calculated and evaluated for the first time. We found a resistance ratio 50 (RR50) of 10.3 (9.7-10.4) for cis-permethrin, which is considered as high resistance. Our results also indicated resistance to deltamethrin (22.6% mortality) and permethrin (53.6% mortality), and a total susceptibility to malathion (100% mortality). Results from this study highlight the importance of the correct use of insecticides within an Integrated Vector Management (IVM) approach and of early detection of resistance to enable Ae. aegypti control in Argentina. More studies are needed to determine the spread of mosquito resistance to pyrethroids.